The ROLE OF TEACHERS IN DEVELOPING SELF- CONFIDENCE OF GRADE 5th ELEMENTARY SCHOOL STUDENTS - Lily Auliya; Umi Fajar Azizah (International Islamic Schools Alliance, 2025)
This study examines the important role of teachers in developing self-confidence in fifth grade elementary school students. Self-confidence, defined as an individual's belief in his or her ability to complete a task or deal with a particular situation, is a fundamental component in personal development. Using a descriptive qualitative method, this research was conducted at SDN 137 Cijerokaso, Bandung, involving two grade V teachers as research subjects. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and conclusion drawing. The results showed that teachers play an important role in creating a supportive learning environment by implementing strategies such as motivational feedback, personalized guidance, and inclusive classroom practices. These strategies have a positive impact on students' academic achievement, social interaction and self-confidence. Despite challenges such as limited teacher patience and communication barriers with students, this study provides practical recommendations to improve pedagogical strategies to effectively support students' confidence development.